Modulatory Effects of Noni (Morinda citrifolia L.) Fruit Polysaccharide Syrup on IgG Production and T Cell Activity - Anwar, La Ode Muhammad; Sasmito, Ediati; Rasydy, La Ode Akbar; Ismoyowati, Tri Wahyuni; Hashim, Salma Hilmy Rusydi; Siregar, Rohani; Hutagaol, Emmelia Kristina; Bratajaya, Cicilia Nony Ayuningsih; Sartika, Aprilina; Sanjaya, Dandi; Rohmah, Hajar Nur Fathur; Ximenes, Joao Manuel Correia (Universitas Negeri Semarang, 2025)
Noni fruit containing polysaccharides, has the potential to be developed into pharmaceutical products such as SPF syrup. The content of noni fruit polysaccharides is known to increase the proliferation of T lymphocyte cells, the regulation of the immune system molecularly, especially with regard to antibodies (IgG), CD4+, and CD8+, is still not widely studied. The aim of this study was to assess the impact of SPF syrup on the modulation of immunoglobulin G (IgG) and T lymphocytes. The study was conducted on female Wistar rats aged 8-9 months, which were given SPF syrup orally at doses of 25, 50, and 100 mg/kgBB for 31 days. Mice were vaccinated against hepatitis B every week. Blood samples were taken on day 31 to measure IgG levels by the ELISA method and T cells (CD4+ and CD8+) by flow cytometry. The results showed that SPF administration had a significant effect on IgG levels (p<0.05), and there were no significant changes in T lymphocyte cells (CD4+, CD8+) (p>0.05). Histopathological examination showed that long-term induction of hepatitis B caused damage to the liver and kidney, but SPF did not affect the condition of these organs. SPF that contains polysaccharides can be an innovative component in immunostimulant formulations.